Ethical Islamic AI Literacy : Model Literasi Artificial Intelligence Berbasis Paradigma Pendidikan Agama Islam - Muhammad Aufa Muis; Chanifudin Chanifudin; Tuti Nuryati; Abdul Basir (CV. Creative Tugu Pena, 2026)
Artificial Intelligence (AI) has significantly transformed educational practices by providing rapid access to information, supporting personalized learning, and assisting academic activities. However, the increasing use of AI in education also raises concerns regarding academic integrity, misinformation, overreliance on technology, and ethical responsibility. In the context of Islamic Religious Education, these challenges require a framework that integrates AI literacy with Islamic educational values and objectives. This study aims to develop the Ethical Islamic AI Literacy (EIAL) model as a conceptual framework for responsible AI utilization from the perspective of Islamic Religious Education. Using a conceptual analysis approach, this study synthesizes contemporary AI literacy discourse with the philosophical foundations of Islamic education, including ta'dib, insan kamil, ulul albab, amanah, sidq, tabayyun, adab, and maslahah. The study proposes five interconnected dimensions of Ethical Islamic AI Literacy: Spiritual Awareness, Critical Verification, Academic Integrity, Responsible Utilization, and Social Benefit. These dimensions position Artificial Intelligence as a learning instrument that supports the formation of knowledgeable, ethical, responsible, and socially beneficial individuals. The EIAL model contributes theoretically by expanding AI literacy discourse through the paradigm of Islamic Religious Education and practically by providing a foundation for curriculum development, academic policies, and ethical guidelines for AI utilization in Islamic educational institutions.